From Ius Valachicum to the vlach folkloric influences within central Europe - Guta, Armand (Balcanica Posnaniensia. Acta et studia, 2015)
This article aims to show the ancient links between the cultural and professional migration of the Vlach (Romanian) shepherds and their folkloric influence upon the Central Slavic ethnographic style and folkloric customs. The migration began more than 1.000 years ago and it was a phenomenon spread over East and North-East Europe and over Central Europe, far away over the River Don to the Caucasian area and through the Balkan Peninsula towards Asia Minor. Concerning the Central European medieval laws from the 17th century till the 18th century, the Vlach shepherds communities had their old oral Vlach jurisdiction and special rights periodically renewed by the Hungarian, German and Polish kings. They played an important military role as frontier guards or defenders of the nobility men. Although from the middle of the 18th century all the Vlach communities were under external domination, their cultural and folkloric heritage was identified to the Central European Slavs’ folklore. It was seen especially in the musical tradition. Many Czech, Polish and Slovak researchers have researched different old folkloric elements and published them in more than 200 abstracts or studies. The results proved that the Romanic elements were about 500 years old or more and influenced much of the Central Slavic folkloric genre. We cannot make an exception of the hundred ancient Romanian words inherited by today’s Slovak shepherds together when many thousands of Vlach ethnographic and folkloric influences lead us towards some interesting conclusions that for a long time the co-existence of the Czech, Slovak and Polish and Vlach population had generated a Slavic-Romanic cultural mix. This genre of the cultural symbioses and its elements are unique in the Central Slavic cultural area.